Evaluation of phase transformation behaviors of zeolite and antibacterial properties against Gram‐positive and ‐negative bacteria. Issue 11 (25th May 2020) - Ishak, Siti Nabihan; Malek, Nik Ahmad Nizam Nik; Yusop, Zulkifli; Williams, Craig D.; Suhartono, Suhartono; Syafiuddin, Achmad
Abstract: This study deals with the synthesis of zeolite from natural kaolinite using hydrothermal treatment and evaluation of its phase transformation behaviors. The synthesized zeolites were modified with silver ion by using the ion exchange method for the enhancement of antibacterial properties. The characterizations were performed by using X‐ray diffraction spectroscopy, Fourier‐transform infrared spectroscopy, field emission scanning electron microscopy, and energy‐dispersive X‐ray. Disk diffusion technique (DDT) was used for the evaluation of the antibacterial property of the modified zeolites. This study observed the transformation of kaolinite into amorphous metakaolin after calcination treatment at 900°C and the successful reconstruction of amorphous metakaolin into synthesized crystal zeolite in the presence of sodium hydroxide as an activating agent. It was also found that the zeolite type A was produced at 100°C, while sodalites were produced at 120 and 140°C. DDT analysis revealed that the modified zeolites showed significant antibacterial capability against Escherichia coli ATCC 11229 and Staphylococcus aureus ATCC 6538. In general, the present study has proven that the zeolites can be synthesized from natural material and can be modified with silver ion to enhance their antibacterial activity. Abstract :